PENYULUHAN PENGELOLAAN PROGRAM DAN IMPLEMENTASI LEMBAGA DAKWAH MAJELIS TA'LIM IHYA AS-SUNNAH DI KECAMATAN SUKAJADI KOTA BANDUNG JAWA BARAT - Neirna Yayah Daryanti; Hemlan Elhany (INSTITUT AGAMA ISLAM NEGERI METRO, 2020)
The results of the study of the management in majlis ta'lim as a place to shape one's character and from education itself become a reference for sukajadi people in practicing every teaching that has been given. In the management of the majlis ta'lim Ihya As-Sunnah, it has only reached the stages of design, organizing activities, given guidance, and also supervision. Then in organizing the activities it has not been carried out as optimally as possible, because in an organizational activity there must be community participation, not to stop in the middle of the road. The motivation carried out by the assembly is only an input, or an appeal to the managers and also the congregation. Sometimes the controls that are exercised by the majlis have not been implemented properly. Ihya As-Sunnah's community empowerment activities that have long been carried out by Ihya As-Sunnah can be studied through 3 visions, namely the da'wah education division, the economic and social division, and the recreation and sports division, through these various visions also Ihya As-Sunnah so that they can always provide good input, provide understanding that can be accepted in the community without being hurt.